Implementasi Akuntansi Melalui Pelatihan Dasar Kepada Siswa Smp Pelita Cemerlang Pontianak - Hengky Leon (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
The purpose of this activity is to provide an increase in students' knowledge and abilities in the field of basic accounting as well as evaluate the shortcomings possessed by students in terms of the field of accounting. The method of activity carried out uses lecture methods, practice methods and evaluation methods. Participants of the activity came from all students of Pelita Cemerlang Junior High School in the eighth grade which amounted to 66 students where four students were not present on the day of implementation. Based on the results of the examination of the results of work practice answers conducted by pelita Cemerlang junior high school students, there are 80 percent who have the ability to answer and solve problems well. The results of this basic accounting training activity received a very good response because the 8th Grade Junior High School students were very careful to follow and listen to every process that was carried out. This activity is expected to have sustainability with the improvement of accounting materials provided so that the development of students' knowledge and abilities is increasingly widespread